2013
DOI: 10.1186/1471-2393-13-187
|View full text |Cite
|
Sign up to set email alerts
|

Partner support in a cohort of African American families and its influence on pregnancy outcomes and prenatal health behaviors

Abstract: BackgroundWe examined how two indicators of partner involvement, relationship type and paternal support, influenced the risk of pregnancy outcomes (preterm birth, low birth weight) and health behaviors (prenatal care, drug use, and smoking) among African American women.MethodsInterview and medical record data were obtained from a study of 713 adult African American women delivering singletons between March 2001 and July 2004. Women were enrolled prenatally if they received care at one of three Johns Hopkins Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 21 publications
2
28
0
1
Order By: Relevance
“…11 Conversely, a recent study among African American women found no association between prenatal partner support and preterm birth, low birth weight, or maternal health behaviors. 29 Our data support the conclusion that women with low antenatal partner support have worse mental health 17,18 and health behaviors 15 than their peers who report high partner support. This is consistent with some, 29 but not all, of the available research.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…11 Conversely, a recent study among African American women found no association between prenatal partner support and preterm birth, low birth weight, or maternal health behaviors. 29 Our data support the conclusion that women with low antenatal partner support have worse mental health 17,18 and health behaviors 15 than their peers who report high partner support. This is consistent with some, 29 but not all, of the available research.…”
Section: Discussionsupporting
confidence: 80%
“…29 Our data support the conclusion that women with low antenatal partner support have worse mental health 17,18 and health behaviors 15 than their peers who report high partner support. This is consistent with some, 29 but not all, of the available research. These differences may reflect the disparate use of indicators and definitions of partner and father involvement used across studies.…”
Section: Discussionsupporting
confidence: 80%
“…Having a partner who did not care was protective against severe PPDs in the sample overall. Research has shown that partner support during the course of a woman's pregnancy is essential to the mother's health and well-being [13,41,44,[62][63][64]. While we did examine discordance between the mother and her partner for pregnancy wantedness, the questions posed to mothers about her own pregnancy wantedness and her partners' were not the same; therefore, actual discordance was difficult to define and with similar questions, may have revealed a greater impact.…”
Section: Discussionmentioning
confidence: 75%
“…One potential mechanism in the relation between marital status or lack of a partner and risk of PPD is the effect of partner support on the mother's perceived social support, which may be linked to PPD [35,36]. While paternal support can be defined through multiple measures: financial support, assistance with child-rearing, the presence of the father on the baby's birth certificate [41][42][43][44][45][46][47], father's own pregnancy wantedness or intention is another aspect of social support related to maternal mental health that has received much less attention in the literature. While few studies have examined the increase in risk of PPD as a result of partner pregnancy intention [16], research on partners' pregnancy intentions and relationship quality has demonstrated the important role that relationship quality and partner intentions play in prenatal care [48], smoking during pregnancy [49], and subsequent high-risk pregnancies [50].…”
Section: Introductionmentioning
confidence: 98%
“…There were four retrospective studies that recruited using birth registries, national surveys, and a hospital setting . Four studies included women at higher risk of PTB, including African American women, or women with low income and/or no health insurance . The percentage of women experiencing PTB in the studies ranged from 5.4% to 22.5%…”
Section: Resultsmentioning
confidence: 99%